The Relationship of Sensory Profile with Behavioral Problems and Psychophysiological Markers in Primary School Children with ASD - M.O. Gromova; N.L. Gorbachevskaya; U.A. Mamokhina; K.K. Danilina (Moscow State University of Psychology and Education, 2021)
Sensory impairments in children with ASD can be one of the main issues that affect social adaptation and integration into society. In present pilot study, the sensory profile of primary school children with ASD investigated using the Sensory Experience Questionnaire SEQ 3.0, which is being validated on a large group of children with developmental disabilities. The relationship between sensory impairments and behavioral difficulties studied in two groups of autistic children: with and without intellectual impairments, 20 participants in each group. The features of their sensory profiles, adaptive behavior, bioelectrical activity of the brain, and the connection between those features investigated. The results showed the effectiveness of the SEQ 3.0 for assessing sensory traits in children with ASD, also the relationship between impaired sensory perception, behavioral characteristics and the pattern of brain bioelectrical activity in children with ASD revealed.